THE SPEAKING PRACTICE OF SEVEN STUDENTS IN THE ENVIRONMENT OF STKIP PARACENDEKIA NW SUMBAWA - Dwi Oktriansyah; Iwan Jazadi; Supriadin (STKIP Paracendekia NW Sumbawa, 2023)
This study is intended to find out the perception of students toward English practice in campus environment, students’ plans and expectation in boosting their speaking skill, and how the students practice their English in campus environment. This study is conducted at STKIP Paracendekia NW Sumbawa. The researcher uses two instruments to find the data needed, namely; observation and interview. The researcher took the fifth semester students of English department as the participants. Based on the data obtained from both instruments used, the findings showed that students perceived about practicing English in campus environment are quite similar. The students also think that practicing English in campus environment is a great way to encourage students’ motivation to practice speaking. The students also supported by their plans and expectations in boosting their speaking ability. Moreover, the students’ ways in practicing English are four. English practice in campus environment includes: English environment, memorize vocabulary, speaking club, and classroom practice. Practicing English also give them more experiences and more knowledge. In addition, the atmosphere tends to be fun and comfortable and it makes them more interested in practicing speaking.